Optimalisasi Prestasi Melalui Pelatihan Program Latihan Cabang Olahraga Futsal pada SMA Negeri 3 Sentani (Indonesian Version) - Muh Syaiful Syam; Ansar CS; Syahruddin Syahruddin; Ibrahim Ibrahim; Muhammad Sadzali; Ade Yuni Sahruni; Ermelinda Yersin Putri Larung; Moh Ifkhal Sianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to increase knowledge and skills in the futsal sports training program at SMA Negeri 3 Sentani. The PkM activity involved 20 participants with a focus on increasing understanding and skills in the quality of futsal game techniques and tactics. The methods used include explaining theoretical understanding, applying theory, as well as direct practice sessions to improve participants' understanding and skills. The results of the activity showed that 3 people or 15% of participants had a good understanding of the pretest, while 17 people or 85% of participants had limited understanding. After participating in the program, the posttest results showed a significant improvement where 18 people or 90% gained good understanding, while only 2 people or 10% still needed additional understanding. The implication of this activity is that it is hoped that teachers who take part in the training will gain increased competence in designing and implementing futsal training programs, so that they can develop students more effectively, improve school achievement, and enrich PJOK learning methods